Community-based Vulnerability Assessment and Risk Mapping for Adaptation Planning in Terai eco-zone, Nepal - Thapa, Pradhan K; Baral, Sony (Journal of Agriculture and Environment, 2013)
Communities have already felt the impact of climate change on their livelihoods. Since the risk of increased negative impacts is high, communities need to understand the climate change patterns, the likely impacts and measures to mitigate the negative impacts. This study was undertaken to assess climate change vulnerability, assess the associated risk and map it, and use these information to prepare adaptation plan. It was found that communities can assess the climate change vulnerability, and map the associated risks. They can prepare their adaptation plan to mitigate the likely negative impacts, and access resources from the local government to implement their action plan. This study has recommended that the community based climate change vulnerability assessment and risk mapping for adaptation planning tools and methodologies developed by this piloting study should be used by the local governments in their regular planning process to address the climate change issues at the community level.